Genetic Variation of Calpastation Gene of Indigenous Bali Cattle (Bos javanicus) in Indonesia - Endang Tri Margawati; Slamet Diah Volkandari; Indriawati Indriawati; Emma M. Svensson (Bogor Agricultural University, Indonesia, 2019)
Calpastatin is one of gene markers affecting meat tenderness. The study aimed to evaluate genetic variation of calpastatin (CAST) gene of Bali cattle (Bos javanicus) in lndonesia. A total of 61 samples consisting of 21 Bali cattle, 22 Ongole cattle (Bos indicus), and 18 Friesian Holstein (FH) cattle (Bos taurus) were applied. The Ongole and FH cattle were involved for breed comparison. DNA was extracted from fresh blood using a High Salt method and measured their quality by a Spectrophotometer. A 523 bp of Calpastatin gene fragment was amplified by Polymerase Chain Reaction and Restriction Fragment Polymorphism (PCR-RFLP) technique with RsaI restriction enzyme for genotyping. Result showed that two variants alleles (C and G) and three genotypes (CC, GC, GG) were found in those Bali, Ongole and FH samples. Allele G was dominant allele with the highest G allele was in Bali cattle population (0.88). The higher percentage of allele C was found in Ongole and Friesian Holstein compared to that in Bali cattle. The Ongole breed tends to have a potential source of lean meat quality. This finding identified that genetic variation of CAST gene was exist in Bali cattle and adapted cattle of Ongole and FH in Indonesian.